Degradation of Fenoprofen Using Activated Carbon Supported Cobalt-Based Catalyst for Heterogeneous Activation of Persulfate - Erdem, Hatice; Erdem, Mehmet (Muş Alparslan Üniversitesi, 2022)
This study aims to investigate the degradation of fenoprofen (FNP) by heterogeneous activation of persulfate (PS) with the activated carbon supported cobalt-based catalyst (Co-AC). The effects of PS concentration, Co-AC dosage, initial pH, and anions on FNP degradation were investigated. FNP was completely degraded and mineralized under optimum operating conditions of 120 min contact time, 0.75 g/L Co-AC, 2 mM PS, natural pH and 25 °C. FNP degradation was found to best fit the pseudo-first order kinetic model. With quenching studies using certain alcohols, the reactive oxygen species effective in degradation were determined and SO4•? was found to be the dominant radical. In addition, the presence of NO3?, SO42? and PO43? anions were found to inhibit FNP degradation. These results indicate that the Co-AC/PS system is a promising and effective process for the degradation of FNP from aquatic environments.

Bu çalışma aktif karbon destekli kobalt-bazlı katalizör (Co-AC) ile persülfatın (PS) heterojen aktivasyonu yoluyla fenoprofenin (FNP) degradsyonununu araştırmayı amaçlamaktadır. FNP degradasyonuna PS konsantrasyonu, Co-AC dozajı, başlangıç pH’sı, ve anyonların etkileri incelenmiştir. 120 dk temas süresi, 0.75 g/L Co-AC, 2 mM PS, doğal pH ve 25 °C optimum işletme koşullarında FNP’nin tam degradasyonu ve mineralizasyonu sağlanmıştır. FNP degradasyonunun pseudo-birinci dereceden kinetik modele en iyi uyduğu bulunmuştur. Belirli alkoller kullanılarak geçekleştirilen söndürme çalışmaları ile degradasyonda etkili reaktif oksijen türleri tespit edilmiştir ve SO4•?‘ün dominant radikal olduğu bulunmuştur. İlaveten, NO3?, SO42? ve PO43? anyonlarının varlığının FNP degradasyonunu inhibe ettiği belirlenmiştir. Elde edilen bu sonuçlar sucul ortamlardan FNP degradasyonu için Co-AC/PS sisteminin umut vaat eden etkili bir proses olduğunu göstermektedir.
Persülfatın Heterojen Aktivasyonu için Aktif Karbon Destekli Kobalt-Bazlı Katalizör Kullanılarak Fenoprofenin Degradasyonu
Keywords: Environmental Engineering; Çevre Mühendisliği